Cover Feature: Interplay Between Charge Accumulation and Oxygen Reduction Catalysis in Nanostructured TiO2 Electrodes Functionalized with a Molecular Catalyst (ChemElectroChem 14/2021). Issue 14 (22nd June 2021) - Kim, Yee‐Seul; Kriegel, Sébastien; Bessmertnykh‐Lemeune, Alla; Harris, Kenneth D.; Limoges, Benoît; Balland, Véronique
Abstract : The Cover Feature shows the competition between catalytic O2 reduction and reversible proton‐coupled charge storage at nanostructured TiO2 thin films, in the presence or absence of an applied potential. More information can be found in the Article by B. Limoges, V. Balland and co‐workers .